The Role of Fake News, Deceptive Propaganda on Social Media in Shaping Public Perceptions - Abro, Amjad Ali; Naseeer, Utaibah; Agha, Sidra (Journal of Development and Social Sciences, 2025)
The study has been designed to analyze the impact of fake news on social media shaping public perceptions. Fake news on social media gained popularity in Pakistan during Imran Khan regime election, prompting individuals to question scientific facts, authentic news, propaganda, perceptions of the public and society standards. The study implied quantitative research data from 356 participants from all districts of Karachi. The data was quantified by using SPSS to validate the results and to present inferences by implying descriptive analysis. This study results indicate that people are highly influenced by fake news and extensive use of social media has been used for changing the perceptions of the public and spreading the propaganda in all spheres of life. The significant influence of fake news and deceptive propaganda on social media is shaping public perceptions. It is recommended there must be fact checking news platforms for the audience and media awareness sessions should available online to stop deceptive propaganda.